Atmospheric pressure non-thermal plasma exposure reduces Pseudomonas aeruginosa lipopolysaccharide toxicity in vitro and in vivo. (November 2019) - Barakat, Muna M.; Dallal Bashi, Yahya H.; Carson, Louise; Graham, William G.; Gilmore, Brendan F.; Flynn, Padrig B.
Abstract: Lipopolysaccharide (LPS) is an endotoxin composed of a polysaccharide and lipid component. It is intrinsically responsible for the pathogenicity of Gram-negative bacteria and is involved in the development of bacterial sepsis. Atmospheric pressure non-thermal plasma is proposed as a potential new approach for the treatment of infected tissue such as chronic wounds, with both antibacterial and wound-healing activities extensively described. Using both the RAW264.7 murine macrophage cell line in vitro assays and the Galleria mellonella insect in vivo toxicity model, the effect non-thermal plasma exposure on LPS-mediated toxicity has been characterised. Short (60 s) non-thermal plasma exposures of Pseudomonas aeruginosa conditioned growth media, membrane lysates and purified P. aeruginosa LPS, resulted in a substantial detoxification and reduction of LPS-induced cytotoxicity in RAW264.7 murine macrophages. Non-thermal plasma exposure (60 s) of purified P. aeruginosa LPS led to a significant ( p < 0.05) improvement in the G. mellonella health index (GHI) score, a measure of in vivo toxicity. These findings demonstrate the ability of short plasma exposures to significantly reduce LPS-induced cytotoxicity both in vitro and in vivo ; attenuating the toxicity of this important virulence factor intrinsic to the pathogenicity of Gram-negative bacteria. Highlights: Intrinsic virulence factors of P. aeruginosa were detoxified with 1-min non-thermal plasma treatment. Non-thermal plasma treatment of P. aeruginosa LPS resulted in detoxification in vitro . Non-thermal plasma treatment of LPS improved the health of G. mellonella in vivo .